Analysis of the Enzymatic Activity of an NS3 Helicase Genotype 3a Variant Sequence Obtained from a Relapse Patient - Provazzi, Paola J. S.; Mukherjee, Sourav; Hanson, Alicia M.; Nogueira, Mauricio L.; Carneiro, Bruno M.; Frick, David N.; Rahal, Paula (PLOS ONE, 2015)
The hepatitis C virus (HCV) is a species of diverse genotypes that infect over 170 million people worldwide, causing chronic inflammation, cirrhosis and hepatocellular carcinoma. HCV genotype 3a is common in Brazil, and it is associated with a relatively poor response to current direct-acting antiviral therapies. The HCV NS3 protein cleaves part of the HCV polyprotein, and cellular antiviral proteins. It is therefore the target of several HCV drugs. In addition to its protease activity, NS3 is also an RNA helicase. Previously, HCV present in a relapse patient was found to harbor a mutation known to be lethal to HCV genotype 1b. The point mutation encodes the amino acid substitution W501R in the helicase RNA binding site. To examine how the W501R substitution affects NS3 helicase activity in a genotype 3a background, wild type and W501R genotype 3a NS3 alleles were sub-cloned, expressed in E. coli, and the recombinant proteins were purified and characterized. The impact of the W501R allele on genotype 2a and 3a subgenomic replicons was also analyzed. Assays monitoring helicase-catalyzed DNA and RNA unwinding revealed that the catalytic efficiency of wild type genotype 3a NS3 helicase was more than 600 times greater than the W501R protein. Other assays revealed that the W501R protein bound DNA less than 2 times weaker than wild type, and both proteins hydrolyzed ATP at similar rates. In Huh7.5 cells, both genotype 2a and 3a subgenomic HCV replicons harboring the W501R allele showed a severe defect in replication. Since the W501R allele is carried as a minor variant, its replication would therefore need to be attributed to the trans-complementation by other wild type quasispecies.